Cloud Computing Trends for the Future - Verma, Garima; Upadhayay, Dhara (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
As the technological landscape continues to conform unexpectedly, the paradigm of cloud computing stands at the forefront of innovation, shaping the destiny of statistics technology. This evaluation paper gives an insightful analysis of the modern-day traits in cloud computing and anticipates the trajectories in an effort to define its future. Through a complete synthesis of the latest literature, this paper explores key trends, demanding situations, and opportunities in cloud computing. It delves into rising technology consisting of part computing, serverless computing, and quantum computing, dropping light on their transformative potential. Additionally, the assessment addresses the evolving position of synthetic intelligence and gadget learning within cloud environments. The problematic interaction among protection, privacy, and compliance inside the cloud is scrutinized, offering nuanced information on the measures necessary to strengthen those important aspects. Moreover, the paper discusses the impact of cloud computing on numerous industries, from healthcare to finance, and the societal implications of its tremendous adoption. By examining current tendencies and forecasting future trajectories, this evaluates objectives to guide researchers, practitioners, and selection-makers in navigating the dynamic landscape of cloud computing and harnessing its full capacity.